2012
DOI: 10.1179/1743281211y.0000000082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituting SiO2with TiO2on viscosity and crystallisation of mould flux for casting titanium stabilised stainless steel

Abstract: During casting of titanium stabilised stainless steel, a gradual increase in TiO 2 content in the molten mould slag from absorption of TiO 2 inclusions causes changes in properties of the mould flux, such as viscosity, solidification temperature and crystallisation behaviour. To simulate this effect mould fluxes were prepared with SiO 2 being substituted with 5 and 10%TiO 2 and viscosity and crystallisation behaviour studied. Experimental results indicate that the substitution of SiO 2 with TiO 2 leads to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Many researchers 4,5) have reported that viscosity of mould fluxes decreases with increased pickup of TiO2 in fluxes during casting. According to the present structural study, degree of polymerization is slightly enhanced with TiO2 increase.…”
Section: (A)-5(c) the Summary Of Deconvolution Results Is Listed Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers 4,5) have reported that viscosity of mould fluxes decreases with increased pickup of TiO2 in fluxes during casting. According to the present structural study, degree of polymerization is slightly enhanced with TiO2 increase.…”
Section: (A)-5(c) the Summary Of Deconvolution Results Is Listed Inmentioning
confidence: 99%
“…The Ti-O bonds are expected to be weaker than Si-O bonds. It was also reported 5) that crystallization ability of mould fluxes also decreases with increase of TiO2. The slightly enhanced degree of polymerization could be one reason for decreased crystallization.…”
Section: +mentioning
confidence: 97%
See 1 more Smart Citation
“…However, B 2 O 3 additions frequently result in a decrease in viscosity. 7,[42][43][44] In pure B 2 O 3 the structure is made up of 3-coordinated BO 3 units arranged in the form of 2-dim rings. However, additions of CaO or Na 2 O result (shown in Eqs.…”
Section: Effect Of B 2 Omentioning
confidence: 99%
“…It is well established that TiO 2 additions result in a decrease in slag viscosity. 11,30,32,39) There are three possible ways TiO 2 can modify the slag structure, namely (i) Ti 4 + is incorporated into the SiO 4 network (ii) Ti acts as a network breaker (by adopting coordination of 5-or 6-) and (iii) by forming TiO 2 -like structures (clusters). 40) There is some dispute which is the dominant mechanism in the geological literature and recent publications are equally inconclusive.…”
Section: Effect Of Tio 2 On Structurementioning
confidence: 99%